2022
DOI: 10.1177/02654075221077280
|View full text |Cite
|
Sign up to set email alerts
|

Affectionate touch in satisfying and dissatisfying romantic relationships

Abstract: Past research has shown consistent benefits associated with and resulting from affectionate touch, though past research is based almost exclusively on highly satisfied and otherwise non-representative samples. The current research used two nationally representative samples to test correlates (Study 1) and anticipated consequences (Study 2) of affectionate touch in romantic relationships. In Study 1, greater kissing frequency was associated with greater individual well-being, and these links were especially pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
3
4
0
Order By: Relevance
“…Similarly, Coan et al (2017) found that under the threat of shock, higher perceived social support is associated with lower neural activity in an extended networks related to regulatory self-control, salience, and vigilance, but only when holding a partner's hand and not friends. Similar findings have been reported in psychological (Horn et al, 2019;Liu et al, 2021;Jakubiak, 2022) and neuroscience (Younger et al, 2010;Morriss et al, 2019) studies.…”
Section: The Brain's Subsystems Form a Complex Adaptive System For Gu...supporting
confidence: 90%
“…Similarly, Coan et al (2017) found that under the threat of shock, higher perceived social support is associated with lower neural activity in an extended networks related to regulatory self-control, salience, and vigilance, but only when holding a partner's hand and not friends. Similar findings have been reported in psychological (Horn et al, 2019;Liu et al, 2021;Jakubiak, 2022) and neuroscience (Younger et al, 2010;Morriss et al, 2019) studies.…”
Section: The Brain's Subsystems Form a Complex Adaptive System For Gu...supporting
confidence: 90%
“…In such circumstances, increasing PDAs would only increase disapproval. Even then, Chris and Robin could increase their private affection-sharing, which is strongly associated with relational well-being, in this study and others (e.g., Jakubiak, 2022). In part, increased private affection-sharing might compensate for the negative effects of network disapproval.…”
Section: Discussionsupporting
confidence: 57%
“…As a logical consequence, a touch’s benefit for an individual’s mental and physical well-being may depend on the perceived closeness to a toucher. In support of this, research on romantic relationships has identified a negative correlation between measures of relationship quality, on one hand, and negative affect, perceived stress, and life dissatisfaction, on the other hand (Coan et al, 2013; Jakubiak, 2022).…”
Section: Discussionmentioning
confidence: 93%